(untitled) (Fiep Bulletin - online, 2014)
Health Education consists of a social intervention tool, which is used by the educator in order to play a role that goes beyond providing vertically knowledge. This education is aimed at questioning reality with those who teach it, by providing them with the means to be agents of their own education, raising awareness and growing up, watching out for their health with autonomy and dignity. This paper aims to analyze health education actions, taking into account scientific production related to the topic, around Latin America. Methodologically speaking, this paper is a quantitative research, sparked by literature, based on scientific articles published in nursing journals from Latin America, through the database Latin American Network Information Center (LANIC). For data collection, it was used the LANIC Etext Collection system. Data were tabulated and analyzed using the Research Analysis and Information System (SIAP), version 6.1.2.0 and displayed in graphs through the application Microsoft Office Professional Excel, version 2013 Plus. The results were divided into publication countries, having Brazil as the top in the ranking (53%), authors titling, in which teachers with a master degree were the ones with the highest score (33%) and also research method, in which the number of Literature Review was noticed as the highest (39%). Therefore, this activity is seen as significant, since it enables an innovative experience, promoting a closer relation and the link between operators and recipients of health education practices.